International groundwater law and the US-Mexico border region - Milanes, Maria E. (International water law series, 2020)
"In International Groundwater Law and the US-Mexico Border Region, Maria E. Milanes provides a study and analysis of the international groundwater law. The regulation and groundwater management along the US-Mexico border reflect the current international trends for management of transboundary groundwater. International Groundwater Law and the US-Mexico Border Region offers a new international legal and institutional framework to manage fossil aquifers and groundwater in conjunctive use with surface water, where specific guidelines and recommendations for water banking can improve water allocation and protect the environment. This framework can be adapted to any region of around the world. The US-Mexico border is the case study selected to apply and demonstrate the efficacy of this legal and institutional framework."